Synopse materiálů k vojvodovskému svatebnímu folkloru - Jakoubek, Marek (Lidé města, 2011)
The subject matter of the article is the wedding ceremony of Vojvodovo Czechs. In the introduction, the author discusses the aims and conceptual positions of ethnography (as understood in the countries of former Czechoslovakia) and social anthropology. Following general discussion, representative texts of both disciplines dealing with the chosen institution are analyzed. The second part of the article presents seven native texts dealing with Czech Vojvodovo weddings, all of them supplemented by short commentary by the author and description of historical context of the documents themselves. In conclusion, the author discusses the differences between and the advantages of the native and the academic descriptions of (not only) the wedding ceremonies of Vojvodovo Czechs.